Synthesis and self-assembly properties of well-defined four-arm star poly(ε-caprolactone)-b-poly(N-vinylpyrrolidone) amphiphilic block copolymers - Mishra A.K.; Ramesh K.; Paira T.K.; Srivastava D.N.; Mandal T.K.; Misra N.; Ray B. (My University, 2025)
Well-defined amphiphilic four-arm star diblock copolymers of poly(ε-caprolactone) (PCL) and poly(N-vinylpyrrolidone) (PNVP) have successfully been synthesized by combining the ring-opening polymerization (ROP) of ε-caprolactone (CL) and xanthate-mediated reversible addition-fragmentation chain transfer (RAFT) polymerization of N-vinylpyrrolidone (NVP). The resulting block copolymer shows the formation of spherical micelles in water as revealed by transmission electron microscopy (TEM) and supported by light-scattering study. The critical micellar concentration (cmc) value of the micelle increases with the increase in the PNVP block length. Hydrodynamic diameter distribution of the micelles decreases with the increase in the PNVP block length. The effective hydrodynamic ratio (R h) remains almost constant over the angles of scattering measurements above the corresponding cmc value. The usefulness of the synthesized star amphiphilic block copolymers was checked by the successful synthesis of silver nanoparticles. Graphical abstract: Well-defined four-arm star poly(ε-caprolactone)-b-poly(N-vinylpyrrolidone) amphiphilic block copolymers are prepared by the combination of ring opening polymerization and xanthate-mediated reversible addition-fragmentation chain transfer polymerization and their self-assembly properties are studied using 1H NMR, fluorescence spectroscopy, dynamic light scattering, and TEM. [Figure not available: see fulltext.] © 2013 Springer-Verlag Berlin Heidelberg.